The mind and sexuality: Introduction to a Psychophysiological Perspective - David L. Rowland; Ion G. Motofei (Journal of Mind and Medical Sciences, 2015)
Cognition and sexuality are two distinct relational functions that are partially interconnected through our mind. Even though medical sciences have progressed substantially over the past decades, the current understanding of the mind psycho-physiology is yet at an early stage. As an example, the “mind-body problem” draws attention to the fact that fundamental aspects related to the understanding of the mind are still unresolved. Thus, it continues to be unclear how abstract ideas and thoughts (which are immaterial in nature, unfolding in an intangible realm) interface (and in some cases, interfere) with the more concrete brain and body (which are physical in nature), thus resulting in an abstract/conscious control of concrete/biological functions of the body; such is the case with processes involved in both cognition and sexuality. Beginning with this seminal paper we therefore intend to approach the psycho-physiology of the mind as an essential element to the understanding of the two (cognitive and sexual) relational functions, using the premises for that model as a basis for understanding of the larger “mind-body problem”.